Public relations - Kokab, Adila; Murslin, Ammara (Society Publishing, 2018)
The main purpose of this book is to introduce you with the concept of public relations. This book is based on the introduction of public relations and what’s it importance. Whether this book is being used for discovering new fields or it is a part of educational program or course, this book will help you with your cause. Therefore, this book is written in very straightforward writing style.